Yoga as a Promising Self‐Care Intervention. The Prevalence and Predictors of Yoga Use Among Adults in Poland. - Roczon, Patryk; Holas, Paweł (Scandinavian Journal of Caring Sciences, 2025)
Background and Aim: Yoga has gained significant attention worldwide as a holistic approach to physical fitness and mental health self‐care. Despite its popularity, gaps persist in understanding its prevalence, drivers for initiation, health advantages and determinants of participation. This study seeks to explore these aspects by examining the prevalence, initial motivations, predictors of engagement and perceived impacts on health and well‐being among a representative sample of Polish adults. Methods: A cross‐sectional online survey was conducted in 2022 with 1065 participants, using quota sampling to approximate a representative sample of the Polish adult population. The study received ethics approval from the University of Warsaw. After data collection, between‐group comparisons and regression analyses were conducted. Results: Findings reveal that approximately 12.2% of Polish adults (4.27 million individuals aged 20 and older) have practised yoga during their lifetime. Female gender and having a higher education were positive predictors of lifetime yoga practice, whereas being aged 45–54 was a negative predictor. The most reported reasons for practising yoga were to improve general well‐being (71.3%), to relax (53.2%) and to improve energy levels (33.9%). Most yoga practitioners perceived enhancements in energy levels, happiness and health (55.0%, 55.0% and 51.4%, respectively). Conclusion: This research highlights the growing interest in yoga among a representative sample of Polish individuals similar to other Western nations, emphasising its perceived benefits for personal well‐being and health enhancement. Future research should investigate these effects using longitudinal and experimental study designs.